COMPUTER SIMULATION OF CLAMPING JAWS WITH ELASTIC COMPENSATING LINKS FOR THIN-WALLED PARTS CLAMPING - Lutsiv, Ihor; Voloshin, Vitalii; Los, Ihor (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The paper deals with the study of clamping jaws with elastic compensating links which have the properties of adaptation to the clamping surfaces of thin-walled work-pieces and ensure the accuracy of their centering. Basing on the method of finite element analysis using a CAD/CAE system, the dependences of the deformations of the jaw clamping section depending on its wall thickness and force loading on the plungers were obtained. According to the computer simulation results the locations of concentration of the maximum equivalent stresses in the clamping jaw with an elastic compensation link and their values are determined. Keywords: adaptive clamping jaw, thin-walled part, centering accuracy, stress-strain condition, elastic deformations